OP024 Long-term safety and efficacy of the anti-MAdCAM monoclonal antibody SHP647 for the treatment of Crohn's disease: the OPERA II study. (16th January 2018) - D'Haens, G R; Reinisch, W; Lee, S D; Tarabar, D; Louis, E; Kłopocka, M; Klaus, J; Schreiber, S; Park, D I; Hébuterne, X; Cataldi, F; Banerjee, A; et al.
Abstract: Background: Despite available treatments, patients with Crohn's disease (CD) often experience symptoms and complications of uncontrolled intestinal inflammation. SHP647 is a fully human IgG2κ anti-MAdCAM monoclonal antibody, in development for induction and maintenance of remission in patients with CD and ulcerative colitis. OPERA II was a 72-week, multicentre, open-label, phase 2 extension study (NCT01298492), designed to assess the long-term safety and efficacy of SHP647 in patients with moderate to severe CD. Methods: Included patients had completed 12 weeks' treatment (placebo or 22.5 mg, 75 mg or 225 mg s.c. SHP647) in OPERA I (NCT01276509), or had a clinical response (≥3-point decrease in Harvey Bradshaw Index [HBI] score) to 225 mg SHP647 in the open-label study, TOSCA (NCT01387594). Patients received SHP647 (75 mg, s.c.) every 4 weeks from baseline to week 72, and were followed up monthly for a further 6 months. Dose de-escalation to 22.5 mg owing to intolerance/AEs, or escalation to 225 mg owing to clinical deterioration/poor response, was allowed as judged by the investigator. Primary endpoints were frequency of AEs, AEs leading to withdrawal and SAEs. HBI scores were used to define remission (score <5) and assessed as exploratory efficacy measures. Results: In total, 268 patients (mean age 36.5 years; 56.3% women) were enrolled and entered the treatment period; 149 completed the study. Mean ± SD HBI score at OPERA II baseline was 4.9 ± 3.01. A total of 1150 and 461 AEs were reported during the treatment and follow-up periods, respectively. The most common treatment-related AEs during treatment were nasopharyngitis (5.6%), arthralgia (6.0%), and headache (5.2%). No patient experienced progressive multifocal leukoencephalopathy. Eighty patients experienced SAEs; these were considered treatment-related in 10 patients. Among patients who had AEs leading to discontinuation ( n = 54) the most common AE was CD flares. Two patients died: one (75 mg) of multiple organ failure after postoperative aspiration following a resection of the terminal ileum. The second (225 mg) died of metastatic neoplasm of unknown primary, with adenocarcinoma identified on cytology. Neither death was considered drug-related. HBI remission and response rates showed no unexpected decay over time (Figure 1). Conclusions: SHP647 was well-tolerated. The sustained HBI response rate suggests efficacy of SHP647 over 72 weeks of treatment. These results add to evidence for the long-term safety and efficacy of SHP647.